Effects of age, BMI and sex on the glial cell marker TSPO — a multicentre [(11)C]PBR28 HRRT PET study - Tuisku, Jouni (Eur J Nucl Med Mol Imaging, 2019)
PURPOSE: The purpose of this study was to investigate the effects of ageing, sex and body mass index (BMI) on translocator protein (TSPO) availability in healthy subjects using positron emission tomography (PET) and the radioligand [(11)C]PBR28. METHODS: [(11)C]PBR28 data from 140 healthy volunteers (72 males and 68 females; N = 78 with HAB and N = 62 MAB genotype; age range 19–80 years; BMI range 17.6–36.9) were acquired with High Resolution Research Tomograph at three centres: Karolinska Institutet (N = 53), Turku PET centre (N = 62) and Yale University PET Center (N = 25). The total volume of distribution (V(T)) was estimated in global grey matter, frontal, temporal, occipital and parietal cortices, hippocampus and thalamus using multilinear analysis 1. The effects of age, BMI and sex on TSPO availability were investigated using linear mixed effects model, with TSPO genotype and PET centre specified as random intercepts. RESULTS: There were significant positive correlations between age and V(T) in the frontal and temporal cortex. BMI showed a significant negative correlation with V(T) in all regions. Additionally, significant differences between males and females were observed in all regions, with females showing higher V(T). A subgroup analysis revealed a positive correlation between V(T) and age in all regions in male subjects, whereas age showed no effect on TSPO levels in female subjects. CONCLUSION: These findings provide evidence that individual biological properties may contribute significantly to the high variation shown in TSPO binding estimates, and suggest that age, BMI and sex can be confounding factors in clinical studies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00259-019-04403-7) contains supplementary material, which is available to authorized users.